Religion, Thick and Thin: On the Development of ‘Religious Studies’ in the American University - Wiebe, Donald (Reviews in religion and theology, 2001)
Book reviewed in this article: Johns Hopkins, The University Gets Religion: Religious Studies in American Higher Education